Sensitivity characteristics of high-birefringence sagnac interferometer. - Liang, Ziyang. (2012)
The sensitivity characteristics of the sensors based on high-birefringence Sagnac interferometer are theoretically analyzed and experimentally verified. We analyze the sensitivity of the sensor in terms of the frequency instead of the wavelength of the light to avoid any approximation and find that the sensitivity can be improved by reducing the length of HBF. The strain, mechanical load and temperature-based experiments are carried out and their experimental results agree well with the theoretical results.